Avaliação das propriedades físicas e mecânicas de UHPC dosados pelo método UNISINOS - Lopes, Raduan Krause (Universidade do Vale do Rio dos Sinos, 2022)
Ultra-High Performance Concrete (UHPC) is the most significant evolution in recent years of cementitious composites, and, due to its mechanical properties combined with high durability compared to conventional concrete (CC), it becomes a structural material with great potential use. Despite this promising potential, its mixing process is sometimes complex to use more widely. In the quest to make the use of UHPC more comprehensive, the UNISINOS dosing method was developed, which made the process of mixing this composite simpler and more rational. However, some parameters that influenced the search for the best mechanical properties of UHPC's still needed to be defined. Thus, the objective of this research was to evaluate the variation of the particle distribution modulus - q - with values of 0.20 and 0.25 and the percentage of cement consumption (15%, 20% and 25%) in obtaining the lowest indices marshaling deviation (IDE) of the method. The compressive and flexural strength properties were evaluated regarding the variation of the two parameters, as well as the workability of the mixtures through the spreading test. The compressive strength results showed that the variation of the modulus q did not show changes in this property, on the other hand, the cement percentage of 20% that generated the lowest IDE's (190 and 180) obtained the highest compressive strength, 151.16 MPa and 147.03 MPa, respectively at 91 days of normal curing. For the results obtained in flexion, the modulus q was also not predominant for significant variations in the values obtained, and as for the percentage of cement linked to the FDI, an inverse correction to the compressive strength is evident, with the highest compression results, showed the lowest values in flexion. Based on the results obtained, mainly the compressive strengths at 28 and 91 days, it is possible to state that the UNISINOS method of measurement is promising in the search for minimum normative mechanical properties for UHPC.
Keywords: Concreto de ultra alto desempenho; Método de dosagem; Propriedades mecânicas; Índice de Desvio de Empacotamento (IDE); Ultra high performance concrete; Method of dosage; Mechanical properties; Packing Deviation Index (IDE); ACCNPQ::Engenharias::Engenharia Civil